Pharmacological Mechanisms of Cryptotanshinone: Recent Advances in Cardiovascular, Cancer, and Neurological Disease Applications - Zheng Z; Ke L; Ye S; Shi P; Yao H (Drug Design, Development and Therapy)
Ziyao Zheng,1 Liyuan Ke,1 Shumin Ye,1 Peiying Shi,2 Hong Yao1,3 1Department of Pharmaceutical Analysis, School of Pharmacy, Fujian Medical University, Fuzhou, 350122, People’s Republic of China; 2Department of Traditional Chinese Medicine Resource and Bee Products, College of Animal Sciences (College of Bee Science), Fujian Agriculture and Forestry University, Fuzhou, 350002, People’s Republic of China; 3Fujian Key Laboratory of Drug Target Discovery and Structural and Functional Research, Fujian Medical University, Fuzhou, 350122, People’s Republic of ChinaCorrespondence: Peiying Shi; Hong Yao, Email peiyshi@126.com; yauhung@126.com, hongyao@mail.fjmu.edu.cnAbstract: Cryptotanshinone (CTS) is an important active ingredient of Salvia miltiorrhiza Bge. In recent years, its remarkable pharmacological effects have triggered extensive and in-depth studies. The aim of this study is to retrieve the latest research progress on CTS and provide prospects for future research. The selection of literature for inclusion, data extraction and methodological quality assessment were discussed. Studies included (1) physicochemical and ADME/Tox properties, (2) pharmacological effects and mechanism, (3) conclusion and bioinformatics analysis. A total of 915 titles and abstracts were screened, resulting in 184 papers used in this review; CTS has shown therapeutic effects on a variety of diseases by modulating multiple molecular pathways. For example, CTS primarily targets NF-κB pathway and MAPK pathway to have a therapeutic role in cardiovascular diseases; in cancer, CTS shows superior efficacy through the PI3K/Akt/mTOR pathway and the JAK/STAT pathway; CTS act on the Nrf2/HO-1 pathway to combat neurological diseases. In addition, key targets of CTS were predicted by bioinformatics analysis, referring to disease ontology (DO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and gene ontology (GO) enrichment analysis, with R Studio; AKT1, MAPK1, STAT3, P53 and EGFR are predicted to be the key targets of CTS against diseases. The key proteins were then docked by Autodock software to preliminarily assess their binding activities. This review provided new insights into research of CTS and its potential applications in the future, and especially the targets and directly binding modes for CTS are waiting to be investigated. Keywords: cryptotanshinone, pharmacological effects, molecular mechanism, bioinformatics analysis